PS 18-15 SALT AND POTASSIUM INTAKE, AND BLOOD PRESSURE IN SOUTH AFRICAN ADULTS: PRELIMINARY RESULTS FROM THE WHO SAGE STUDY. (September 2016) - Schutte, Aletta; Ware, Lisa; Charlton, Karen; Kowal, Paul
Abstract : Objective: Attempts to curb the hypertension epidemic have resulted in varied salt reduction strategies across the globe. In June 2016, South Africa implements legislation limiting maximum sodium levels in a range of foods previously identified as contributing significantly to population sodium intake. This study was designed to establish baseline sodium and potassium intake, as well as blood pressure (BP) prior to legislation coming into effect. Design and Method: Participants were recruited using a nested cohort design within the World Health Organization Study on global AGEing and adult health (WHOSAGE), a multi-national longitudinal study of the health and well-being of adults and the ageing process (18+ years, with an emphasis on adults 50+ years). The SAGE-South Africa cohort consists of randomly selected households (n = 4583 adults) across the country. Spot and 24-hour urine samples were collected in a random sub-sample and sodium, potassium and creatinine analysed. BP, anthropometry, and sociodemographic data were collected at the same time, as part of SAGE Wave2. Results: Median age of the group was 55 years (IQR 24; n = 450; 80% female). Daily salt and potassium excretion varied greatly, with a median of 6.7 g salt/day (1–43 g/day), 1.3 g potassium/day (0.2–8.5 g/day) and a molar sodium-to-potassium ratio of 3.3 (0.3–16.0). Previous diagnosis of hypertension was low (22%) but BP readings and medication use revealed 42% to be currently hypertensive (71% untreated; 15% treated uncontrolled; 14% treated controlled). In comparison to WHO recommendations, 69% had a salt intake above 5 g/day, 91% had a potassium intake below 90 mmol/d and 96% had Na:K ratio >1. Only 3 (<1%) participants achieved all three recommendations. Conclusions: Given the high prevalence of hypertension and untreated hypertension among South African adults, the sodium legislation is a welcome step in reducing population BP. Further investigation and intervention for increasing population potassium intakes could be a next step.